PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH EXPERIENTIAL MARKETING TERHADAP PEMBELIAN ULANG TIKET PESAWAT PADA PT JASA NUSA WISATA DENPASAR - Reynard Olii, Kevin Reno; Nurcaya, I Nyoman (E-Jurnal Manajemen, 2016)
This study aims to determine the role of customer satisfaction in mediating the effects of experiential marketing to re-purchase tickets. This study uses primary data was collected using a questionnaire as a research instrument that is spread on the respondent. Respondents are consumers PT Jasa Nusa Wisata who make a purchase of at least 2 times. The sampling method using purposive sampling. The number of respondents who used for this study is 190 respondents. The analysis technique used Path Analysis. Based on the analysis found that experiential marketing that positive and significant impact on customer satisfaction. Customer satisfaction positive and significant impact on repeat purchases. Experiential Marketing positive and significant impact on repeat purchases. Customer Satisfaction Variables significantly mediates the effect of Experiential Marketing to Purchase Repeat.
Keywords: experiential marketing, customer satisfaction, repeat purchases